Penerapan Konsep Marketplace pada Bisnis Laundry dengan menggunakan Framework Multiplatform Flutter - Satriany Lauri; Djoni Haryadi Setiabudi; Agustinus Noertjahyana (Jurnal Infra, 2020)
Over time, more and more laundry companies are threatened by their existence because of the lack of containers to accommodate laundry needs from customers and ultimately resulting in fewer and fewer customers, with a variety of reasons owned by customers such as the distance that does not allow, and customer ignorance of quality laundry that is automatically price and fulfillment. When viewed from the aspect of the customer, the user needs a system that can facilitate the user in meeting the need to wash, both in terms of time efficiency, and the affordability of the place. When viewed from the aspect of the laundry owner, the laundry owner needs a system that can be a bridge between the user and the owner, so that the laundry owner can enter a wider market. So when viewed from these two aspects, both parties need a concept or system that connects the two parties, namely the concept or marketplace system. The mobile laundry application with the marketplace concept aims to increase the user's time efficiency in meeting washing needs, and provide greater access to enter a broader market for laundry entrepreneurs. This application will be created using the Dart language using Visual Studio Code. This application helps customers to choose various kinds of laundry, with various categories of choices, customers also have features such as chat, notifications, customer profile, determine the date and time of delivery, choose the address of delivery and delivery, and features to view details of the order that is have been done. In addition this application also helps laundry owners to enter, edit, and delete categories that they have, and laundry owners also have a notification, chat, profile laundry owner, and features to update order status. The test results show that this application runs well on devices such as Android 8.0 (Oreo), and also the marketplace concept is proven to be applicable to the laundry business in terms of the system by having a web admin as a third party that managing the marketplace where the seller (the laundry) and the buyer (the customer) meet, and in terms of the convenience provided to the customer and laundry side.